Tuning Optical Properties by Controlled Aggregation: Electroluminescence Assisted by Thermally‐Activated Delayed Fluorescence from Thin Films of Crystalline Chromophores. Issue 71 (17th November 2020) - Haldar, Ritesh; Jakoby, Marius; Kozlowska, Mariana; Rahman Khan, Motiur; Chen, Hongye; Pramudya, Yohanes; Richards, Bryce S.; Heinke, Lars; Wenzel, Wolfgang; Odobel, Fabrice; Diring, Stéphane; Howard, Ian A.; et al.
Abstract: Several photophysical properties of chromophores depend crucially on intermolecular interactions. Thermally‐activated delayed fluorescence (TADF) is often influenced by close packing of the chromophore assembly. In this context, the metal‐organic framework (MOF) approach has several advantages: it can be used to steer aggregation such that the orientation within aggregated structures can be predicted using rational approaches. We demonstrate this design concept for a DPA‐TPE (diphenylamine‐tetraphenylethylene) chromophore, which is non‐emissive in its solvated state due to vibrational quenching. Turning this DPA‐TPE into a ditopic linker makes it possible to grow oriented MOF thin films exhibiting pronounced green electroluminescence with low onset voltages. Measurements at different temperatures clearly demonstrate the presence of TADF. Finally, this work reports that the layer‐by‐layer process used for MOF thin film deposition allows the integration of the TADF‐DPA‐TPE in a functioning LED device. Abstract : A crystalline, oriented thin film with green electroluminescence is illustrated. Enforced by SURMOF assembly, controlled aggregation of the DPA‐TPE linker chromophore turned‐on TADF process, boosting the luminance of the crystalline thin film.